Accuracy of angle and position of the cup using computed tomography-based navigation systems in total hip arthroplasty. (17th July 2013) - Iwana, Daiki; Nakamura, Nobuo; Miki, Hidenobu; Kitada, Makoto; Hananouchi, Takehito; Sugano, Nobuhiko
Abstract: Objective : The objectives of this study were to evaluate the accuracy of computed tomography (CT)-based navigation and to investigate whether the level of surgeon experience affects the accuracy of cup positioning under navigation. Methods : This study investigated 117 hips in 103 patients who underwent primary total hip arthroplasty (THA) by 7 surgeons using a CT-based navigation system. Pre- and postoperative CT images were matched using a volume registration technique. Postoperative cup angles and positions were then measured using the same pelvic coordinates, and results were compared for experienced and inexperienced surgeons. Results : The mean absolute error of the cup angle was 1.8 ± 1.6° for inclination and 1.2 ± 1.1° for anteversion. The mean absolute errors of cup position were 1.9 ± 1.5 mm, 1.4 ± 1.2 mm, and 1.9 ± 1.3 mm on the x-, y- and z-axes, respectively. No significant differences in accuracy were identified between experienced and inexperienced surgeons. Conclusions : The absolute spatial error of cup position was ≤2 mm for each axis, and the angle error was ≤2° for the angles of inclination and anteversion. This navigation system could therefore help surgeons perform accurate cup placement irrespective of the surgeon's level of experience.